"A 'Golden Child' for Investors": the assetization of urban childcare property in NZ. Issue 10 (26th November 2021) - Gallagher, Aisling
ABSTRACT: Childcare services are a key part of the social infrastructure of cities. Yet childcare property has recently been signaled as one of the fastest growing alternative real estate investment opportunities within a number of neoliberalized childcare markets. Shedding light on this phenomenon, in this paper I examine how urban childcare property has become an attractive option for individual investors in Aotearoa/New Zealand. Speaking to the literature on urban financialization and the neoliberalization of care, I examine the relationship between the privatization of childcare services and the growth of the childcare property market; the work of property agents as key intermediaries in shaping the terrain of investment into childcare property; and the passive investor subject which is envisioned. Ultimately, I argue that the role of the state has been crucial to the formation of this recent property investment trend in NZ, setting in place the conditions for assetization to occur.